Effect of a 5-month exercise program on blood pressure and glucose: A case study of a 68-year-old woman with diabetes mellitus type II and hypertension - Kekelekis Afxentios; Knechtle Beat; Nikolaidis Pantelis T. (Sciendo, 2020)
Introduction: The aim of the present case study was to examine the effect of a 5-month exercise intervention on glucose and hypertension level of a patient with diabetes mellitus.